Cultural and Heritage Connections between Malaysia and India: A Shared Legacy - Velmurugan, S; Rajalakshmi, A (Journal of Indian Studies (இந்திய ஆய்விதழ்), 2025)
India and Malaysia share a rich and enduring bilateral relationship, shaped by deep historical, cultural, economic, and strategic ties. Their collaboration is evident across diverse sectors, including trade, defense, education, and technology, with both nations actively engaged in regional agreements such as ASEAN and RCEP. The influence of Indian culture, particularly through the Tamil diaspora, plays a significant role in fostering cultural exchanges, while shared traditions, festivals, and religious practices further strengthen these ties. Joint efforts in fields like medical tourism, space research, and sustainability highlight the depth of their cooperation. Both countries also collaborate on regional security, particularly in maritime security and counterterrorism initiatives. This paper explores the cultural and heritage connections between Malaysia and India, emphasizing their shared legacy and the areas of mutual benefit that continue to shape their partnership in the contemporary world. India dan Malaysia berkongsi hubungan dua hala yang kaya dan berkekalan, dibentuk oleh ikatan sejarah, budaya, ekonomi, dan strategik yang mendalam. Kerjasama mereka jelas merentas pelbagai sektor, termasuk perdagangan, pertahanan, pendidikan, dan teknologi, dengan kedua-dua negara terlibat secara aktif dalam perjanjian serantau seperti ASEAN dan RCEP. Pengaruh budaya India, terutamanya melalui diaspora Tamil, memainkan peranan penting dalam memupuk pertukaran budaya, manakala tradisi, perayaan, dan amalan keagamaan yang dikongsi bersama mengukuhkan lagi ikatan ini. Usaha bersama dalam bidang seperti pelancongan perubatan, penyelidikan angkasa lepas, dan kelestarian menonjolkan kedalaman kerjasama mereka. Kedua-dua negara juga bekerjasama dalam keselamatan serantau, terutamanya dalam keselamatan maritim dan inisiatif antiterorisme. Kertas kerja ini meneroka hubungan budaya dan warisan antara Malaysia dan India, menekankan legasi bersama mereka dan bidang-bidang manfaat bersama yang terus membentuk perkongsian mereka dalam dunia kontemporari.